2014
DOI: 10.1016/j.jpedp.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory viral infections in pediatric cancer patients undergoing chemotherapy

Abstract: Objective: to estimate the prevalence of infection by respiratory viruses in pediatric patients with cancer and acute respiratory infection (ARI) and/or fever. Methods: cross-sectional study, from January 2011 to December 2012. The secretions of nasopharyngeal aspirates were analyzed in children younger than 21 years with acute respiratory infections. Patients were treated at the Grupo em Defesa da Criança Com Câncer (Grendacc) and University Hospital (HU), Jundiaí, SP. The rapid test was used for detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…A research conducted in the pediatric oncology sector showed similar data to those of this study. In such research, the participants had median age of 12 years (12) .…”
Section: Discussionmentioning
confidence: 99%
“…A research conducted in the pediatric oncology sector showed similar data to those of this study. In such research, the participants had median age of 12 years (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viruses have become a frequently observed source of infection in about half of the patients with respiratory tract infections in children undergoing chemotherapy [10]. Koskenvuo et al [11] documented the presence of respiratory infection in 44% of the cases of children and adolescents with leukaemia and fever, and Srinivasan et al [12] observed rates of 75% in their study.…”
Section: Introductionmentioning
confidence: 97%
“…Immunocompromised patients, such as those with cancer and hematopoietic stem cell transplantation, have a higher risk for respiratory infections, and single or mixed respiratory viruses are frequently detected in those with acute respiratory symptoms . Defects in innate and adaptive immunity coupled with damage in the mucosal membrane and frequent exposure to a healthcare environment contribute to increased morbidity and mortality of respiratory infections in these patients . In healthy children, respiratory viruses are usually confined to the upper respiratory tract; in immunocompromised patients, progression to the lower respiratory tract is a more frequent and feared complication .…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory infections are major causes of febrile episodes in patients with pediatric cancer . These patients often are initiated on broad‐spectrum antibiotics to cover serious bacterial diseases, leading to unnecessary increased exposure to antibiotics and the potential emergence of antibiotic resistance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation